An approach to the images in José María Eguren's «Syhna la blanca» - Arbulú Zumaeta, Priscila (2022)
The present article intends to approach the images presented in the poem «Syhna la blanca», by José María Eguren, published in Simbólicas, in 1911; likewise, from previous interpretations, his images are analyzed. For this, it takes into account the reception of the work and the author's context.